Growth and Functional Development in 6 to 10 Years Old Soccer Players: Constraints and Possibilities - Marcio Domingues (The Society of Aging and Physical Activity (SAPA), 2013)
Sport and more specifically football is an important asset in youth lives. It is widely considered that biological maturity influences physical performance. Relationships between body size and performance are partly confounded by age. In fact, age is positively associated to strength and motor performance, even when height and weight are controlled. Studies on young footballer have been started to consider the potential impact of variation on growth and biological maturity status upon sport-specific football skills. Some authors suggest that physical training should have a low priority until the late puberty and then the time could be devoted to other types of training such as focusing on technical aspects. However, the question remains that is this due to low trainability or inadequacies of training programs? A brief review of the literature was conducted with three specific exclusion criteria including the age of footballers, relation of age with performance, and studies on football. There are critical periods in the life of a young person, in which the effects of training can be maximized. Thus, a special attention should be paid to developing football skills by regarding the performance and full respect to youth development. Many papers have been published on functional capacities and dimensions in pre-adolescence and adolescence, but less information are available concerning the ages between 6 and 10. Hence, this paper aims to highlight some aspects of this age period and provide an understanding of important aspects of growth, development, and maturation is particularly important, as a youngster's football performance may depend heavily on gender and biological age and state.